PERENCANAAN DAN PERANCANGAN ISLAMIC CENTER DI KABUPATEN LUMAJANG - Ricky Ravsyan Alhafez; Bambang Wicaksono; M. Solikhudin (UNIVERSITAS INDO GLOBAL MANDIRI, 2018)
The Islamic Center in Lumajang district is a religious institution as a center for the development and development of religion and Islamic culture in a continuous and directed, so as to realize an active and dynamic religious life in the community towards the full development of people, which emphasizes on non-formal education in a mass. The pattern of activities of Islamic Center in Lumajang Regency which will be planned to have the scope of service area of Lumajang Regency and its surroundings, the emphasis of operational activities that include ritual, social and commercial activities with attention to the potential of Islam and local cultural characteristic so that its existence can be an integral part of growth society is increasingly dinamis.Pendekatan on the analysis of the Islamic Center in Lumajang District Planning approach Islamic Center in Lumajang using suppression approach that includes design: geometry approach in Islamic architecture, facade precedent geometry in architecture, approach to offenders and activity, and the amount of space studies. The main activity groups include: building guidance of ummah (such as mosque, multipurpose room, da'wah media), administration and management building (management building), education building (Madrasyah, library building). Supporting activity groups include: (food court), service activities service buildings.Keywords: Planning, Islamic Center, Lumajang District